Pancreatic lipase inhibitory activity of butterfly pea flower (Clitoria ternatea) Kombucha - Roka Aji, Oktira; Putri , Diah Asta; Putri, Nida’a Fauziyyah (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
Preventing the action of pancreatic lipase is believed to be an effective method for treating obesity. Pancreatic lipase inhibitor act by suppressing the activity of pancreatic lipase, leading to a decrease in lipid absorption. Kombucha is a traditional fermented drink believed to have numerous health benefits, including as anti-obese. It can be produced using a range of substrates, such as butterfly pea flowers. The aim of this research was to investigate the inhibiting activity of kombucha made from butterfly pea flowers towards pancreatic lipase. The fermentation parameters monitored in this study included changes in cell density (OD600), the dry weight of the kombucha mushroom, pH, reducing sugar content, and the % titratable acid. The total phenol and total flavonoid content were also analyzed before and after fermentation. The inhibitory effect on pancreatic lipase of butterfly pea flower kombucha was presented as an IC50 value. The findings indicated that as fermentation progressed, the pH level and amount of reducing sugar decreased while the % titratable acid, cell density (OD600), and dry weight of the kombucha mushroom increased. The phenol and flavonoid content of butterfly pea kombucha was found to be greater compared to that of butterfly pea infusion, with respective levels of 0.040 mg GAE/g and 0.017 mg QE/g. This study confirms that butterfly pea flower kombucha has the ability to inhibit pancreatic lipase in vitro with an IC50 value of 162.83 μg/mL. Compared to butterfly pea flower tea infusion, butterfly pea flower kombucha has been found to be more effective in inhibiting pancreatic lipase. Thus, butterfly pea flower kombucha might be a promising candidate for being developed as an agent for combating obesity.